Arabic and its Alternatives Religious Minorities and their Languages in the Emerging Nation States of the Middle East (1920-1950) - Murre-van den Berg, Heleen; Sanchez, Karène; Baarda, Tijmen C. (Christians and Jews in Muslim Societies, 2020)
Arabic and its Alternatives discusses the complicated relationships between language, religion and communal identities in the Middle East in the period following the First World War, taking its starting point in the non-Arabic and non-Muslim communities of the region. Readership: All those interested in the modern and contemporary history of the Middle East, in religious and linguistic minorities, in identity formation and nationalism and in the relationship between language and religion.